Tree visualization system and method based upon a compressed half-plane model of hyperbolic geometry - Hida, Yozo; Lamping, John O.; Rao, Ramana B. (2005)
A node-link structure is displayed within a display area, having a narrow rectangular shape with an edge along one side acting as a horizon of a hyperbolic space half-plane. Lower level node features that share a parent node feature have centers of area positioned on the display in order along a line parallel with the horizon, with sufficiently similar spacings along an axis perpendicular to the horizon from the region around a parent node feature, and with sufficiently similar spacings in a dimension parallel to the horizon from adjacent node features along the line, that the lower level node features sharing the parent node feature are perceptible as a group of related node features. The half-plane model with compression is used for layout of the node-link data, and the hyperbolic layout data is mapped to a Euclidean space for display.